Experimental Study of Welding Effect on S690Q High Strength Steel Butt Joints. Issue 3 (16th September 2019) - Chiew, S.P.; Cheng, C.; Zhao, M.S.; Lee, C.K.; Fung, T.C.
ABSTRACT: In this study, welding effects on grade S690Q high strength steel butt joint are investigated experimentally in terms of microstructure, micro‐hardness, and tensile behaviour. Three butt joints with 16 mm thickness are fabricated with reheated, quenched and tempered S690Q high strength steel (HSS) plates by using Shielded Metal Arc Welding with different welding heat inputs. Post‐welding microstructure transformation is revealed in base material, coarse‐grained heat‐affected zone (CGHAZ), fine‐grained heat‐affected zone (FGHAZ) and tempering zone. It is found that the main microstructure of S690Q high strength steel is tempered martensite. After welding, the microstructure is transformed to granular bainite in CGHAZ and to ferrite & cementite in FGHAZ. While, in tempering zone, some temper martensite decomposed to ferrite. Then, micro‐hardness tests performed for the butt joints confirmed the existence of a soft layer within the HAZ due to the microstructure transformation. The HAZ width increased when higher welding heat input is adopted. Subsequent coupon tensile tests showed that all the welded joint fractured within the HAZ. The tensile strength of the butt joints deteriorated with the increase of the welding heat input since the soft layer became bigger in HAZ.